Speculative Retail Trading and Asset Prices - Han, Bing; Kumar, Alok (Journal of Financial and Quantitative Analysis, 2013)
Abstract This paper examines the characteristics and pricing of stocks that are actively traded by speculative retail investors. We find that stocks with high retail trading proportion (RTP) have strong lottery features and they attract retail investors with strong gambling propensity. Furthermore, these stocks tend to be overpriced and earn significantly negative alpha. The average monthly return differential between the extreme RTP quintiles is −0.60%. This negative RTP premium is stronger among stocks that have lottery features or arelocated in regions where people exhibit stronger gambling propensity. Collectively, these results indicate that speculative retail trading affects stock prices.